"In water" synthesis of bis(indolyl)methanes: a review. Issue 19 (2nd October 2021) - Khanna, Leena; Mansi; Yadav, Shilpa; Misra, Neeti; Khanna, Pankaj
Abstract: Bis(indolyl) methane (BIM) derivatives have shown numerous biological properties which has influenced the scientific fraternity to explore the length and breadth of their synthesis. Mostly, the procedure involves a catalytic electrophilic substitution reaction of indoles with various aldehydes and ketones. However, many variations have been applied from time to time to promote this reaction under green conditions. The use of water as a solvent in organic synthesis, has gained much attention due to economic and eco-friendly reasons. It has also been observed that the reactions under aqueous conditions have shown high reactivities and chemo-selectivity, which are not found in organic media. "In water synthesis" of BIMs has gained considerable recent importance and several methods have been developed. Thus, in this review we have summarized different synthetic protocols used to prepare BIMs under aqueous conditions in the last fifteen years.